HIGH-INTENSITY INTERVAL TRAINING (HIIT) FOR ELDERLY: EFFECTS ON PHYSICAL FITNESS AND OVERALL HEALTH - CHOKTAWEEPANICH, Bhakbhum; Seubtrakul TANTALANUKUL, Seubtrakul; KANJANAPRADIT, Nukan (Journal of Sports Science and Technology, 2024)
High-Intensity Interval Training (HIIT) has gained increasing attention for promoting health among elderly due to its effectiveness in improving physical fitness and overall health. This comprehensive review aims to synthesize and analyze the latest scientific evidence on HIIT for elderly, examining its multifaceted effects on health and well-being. The review covers key aspects including physiological principles, adaptation of protocols, effects on various health parameters, comparison with other exercise modalities, application of technology, implementation guidelines for health promotion programs, challenges and considerations, and future research trends. The review finds that HIIT demonstrates significant benefits across multiple health domains in elderly. These benefits include (1) Cardiovascular improvements: Increasing maximal oxygen uptake (VO₂max), Enhancing heart function, Improving blood pressure control, Optimizing blood vessel function ( 2 ) Musculoskeletal benefits: Increasing muscle strength and power,Enhancing physical function, Improving balance and mobility, Maintaining bone density (3) Metabolic advantages:Supporting weight management, Improving insulin sensitivity, Enhancing fat metabolism, Optimizing body composition (4) Cognitive and psychological benefits: Supporting cognitive function, Enhancing mood and well-being, Reducing depression risk, Improving quality of life (5) Functional improvements: Enhancing activities of daily living, Supporting independence, Improving social interaction, Reducing fall risk However, implementing HIIT requires careful consideration of safety and appropriate adaptation to the physical condition of each older individual. The use of modern technologies, such as mobile applications and vital sign monitoring devices, can enhance the efficiency and safety of HIIT programs. Guidelines for promoting HIIT in elderly should include appropriate program design,education and training, integration with social activities, and regular monitoring and evaluation. Furthermore, there is a need for additional research in several areas, including: Long-term effects of HIIT on multiple health parameters,Optimal protocols for different health conditions, Integration with other lifestyle interventions, Cost-effectiveness in various healthcare settings, Implementation strategies for different populations. In conclusion, HIIT shows high potential for promoting comprehensive health benefits among elderly but requires careful and appropriate implementation. The combination of suitable program design, supportive technology, appropriate safety measures, and psychological support will contribute to the successful application of HIIT in promoting healthy aging and enhanced quality of life for elderly. (Journal of Sports Science and Technology 2024; 24(2):19-35) (Received: 8 Julyl 2024, Revised: 10 November 2024, Accepted: 22 November 2024) KEWWORD: Cardiovascular Health/ Cognitive Function/ Psychological Well-Being/ Functional Capacity/Exercise Technology *Corresponding author: Bhakbhum CHOKTAWEEPANICH Faculty of science and technology, Uttaradit Rajabhat University Email: pakphomc@gmail.com